Preparation method of composite catalytic material capable of degrading rhodamine B in organic wastewater

By assembling the composite photocatalytic material of BiCu2O6STe5/Bi2BrTmO4 nanocrystals on the surface of the foam iron matrix, the problem of low efficiency and poor stability of photothermal activation of persulfate in the prior art is solved, and high efficiency and stable Luodan is achieved It demonstrates the degradation effect of B and is suitable for industrial treatment.

CN119281402APending Publication Date: 2025-01-10NORTH CHINA UNIVERSITY OF TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411648183.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The existing photothermal activated permonosulfate catalytic technology is inefficient and poorly stable when degrading Rhodamine B organic dye wastewater, limiting its application in industrial treatment.

Method used

Poly(acrylamide-isodecyl acrylate) is synthesized by loading isodecyl acrylate on the surface of the foamed iron matrix and synthesizing poly(acrylamide-isodecyl acrylate) through polymerization, and then assembling BiCu2O6STe5/Bi2BrTmO4 nanocrystals on its surface to form a composite photocatalytic material to improve photothermal activation Efficiency of persulfate.

Benefits of technology

The prepared composite catalytic material has a wide absorption spectrum and stable photothermal activation properties, which significantly improves the degradation efficiency of rhodamine B and is suitable for industrial treatment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119281402A_ABST
    Figure CN119281402A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a composite catalytic material capable of degrading rhodamine B in organic wastewater. The preparation method comprises the following steps: (1) loading isodecyl acrylate on the surface of a foam iron matrix; (2) synthesizing poly (acrylamide-iso-decylacrylate) on the surface of the foam iron matrix by utilizing a polymerization reaction between an acrylamide monomer and an iso-decylacrylate monomer; and (3) assembling a BiCu2O6STe5 / Bi2BrTmO4 nano crystal on the surface of the poly (acrylamide-iso-decylacrylate). The composite catalytic material prepared by the method disclosed by the invention has a wide absorption spectrum and excellent and stable performance of photo-thermally activating peroxymonosulfate to degrade rhodamine B organic dye.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of organic dye wastewater treatment, in particular to a method for preparing a composite catalytic material capable of degrading rhodamine B in organic wastewater. Background Art

[0002] Triphenylmethane dyes are organic compounds with triphenylmethane as the parent structure and their derivatives. Due to their wide chromatographic range, bright colors and good dyeing effects, these dyes have been widely used in the textile, leather, papermaking, paint and other industries. Rhodamine B (RhB) is a typical triphenylmethane basic dye that is soluble in water. In the production process of the textile, leather, papermaking and paint industries, a large amount of organic dye wastewater containing Rhodamine B is produced. In such wastewater, Rhodamine B is difficult to remove by biodegradation, is easy to migrate, and has carcinogenic and teratogenic toxicity, posing a major threat to human health and the ecological environment.

[0003] Persulfate can activate and generate sulfate radicals (SO4 - ·), whose oxidation potential can reach 2.5V to 3.1V, can oxidize and degrade most organic pollutants. However, the current method of using peroxymonosulfate to activate SO 4- The efficiency of oxidative degradation is extremely low, making it difficult to effectively treat organic dye wastewater containing Rhodamine B.

[0004] Persulfate is activated and decomposed to generate strong oxidizing SO4 - The efficiency can be improved through thermal activation. Photothermal materials are a class of materials with photothermal conversion properties. They work under light conditions due to the localized surface plasmon resonance (LSPR) effect, the generation and relaxation effect of electron-hole pairs, and the molecular thermal vibration effect. The photothermal effect of photothermal materials can significantly improve the activation of persulfate to produce SO4 - ·, thereby effectively degrading and treating organic dye wastewater containing Rhodamine B, which will be a green and environmentally friendly technical approach.

[0005] However, there are still some problems with the current technology of using photothermally activated persulfate to catalyze the degradation of rhodamine B. The prepared composite material has a narrow absorption spectrum, resulting in a low efficiency of photothermally activated persulfate to degrade rhodamine B, and poor stability of the degradation process. These defects limit its application in large-scale and efficient industrial treatment of organic dye wastewater containing rhodamine B. Therefore, further research and improvement are needed to meet industrial needs. Summary of the invention

[0006] In order to overcome the shortcomings of the prior art, the present invention provides a method for preparing a composite catalytic material capable of degrading Rhodamine B in organic wastewater. The composite catalytic material prepared by the method has a wide absorption spectrum and excellent and stable performance of photothermal activation of peroxymonosulfate to degrade Rhodamine B organic dye.

[0007] The technical solution adopted by the present invention to solve the technical problem is:

[0008] The present invention provides a method for preparing a composite catalytic material capable of degrading rhodamine B in organic wastewater, comprising the following steps:

[0009] Step [1]: loading isodecyl acrylate on the surface of the foamed iron substrate;

[0010] Step [2] synthesizing poly(acrylamide-isodecyl acrylate) on the surface of the foamed iron matrix by a polymerization reaction between acrylamide monomer and isodecyl acrylate monomer;

[0011] Step [3] assembles BiCu2O6STe5 / Bi2BrTmO4 nanocrystals on the surface of the poly(acrylamide-isodecyl acrylate).

[0012] Preferably, the step [1] specifically includes the following operations:

[0013] a1. Acrylic acid, 98% concentrated sulfuric acid and isodecyl alcohol were added to deionized water and mixed to form a base solution A; phosphorus pentachloride was added to carbon tetrachloride and mixed to form a base solution B; a certain amount of base solution A was mixed with base solution B to obtain a load solution;

[0014] a2. Immerse the foamed iron in an isodecyl acrylate loading liquid, heat to 80-130°C, react for 2-4 hours, cool to room temperature, and dry at room temperature for 10 to 14 hours to obtain a foamed iron loaded with isodecyl acrylate on the surface, recorded as intermediate A.

[0015] Preferably, in step a1, the amount of acrylic acid added to each liter of the base liquid A is 230-270 mL, the amount of isodecyl alcohol added is 140-210 mL, the mass concentration of sulfuric acid in the base liquid A is 5-10%; the amount of phosphorus pentachloride added to each liter of the base liquid B is 20-40 g; and the volume ratio between the base liquid A and the base liquid B in the load liquid is 3-5:1-2.

[0016] Preferably, in step a2, the weight of the foamed iron matrix immersed in each liter of the loading liquid is 150-200 g.

[0017] Preferably, the step [2] specifically includes the following operations:

[0018] b1. Add acrylic acid, isodecyl acrylate and azobisisobutyronitrile to ethanol and mix to form a base liquid C; add acrylamide to deionized water to form an additive liquid; mix a certain amount of the additive liquid with the base liquid C to obtain a polymer liquid.

[0019] b2. The intermediate A is immersed in the polymerization solution, heated to 70-100 ° C, reacted for 10-14 hours, cooled to room temperature, and dried at room temperature for 8 to 12 hours to obtain a foam iron loaded with polyacrylamide-isodecyl acrylate on the surface, recorded as intermediate B.

[0020] Preferably, in step b1, the amount of acrylic acid added to each liter of the base liquid C is 60-100 mL, the amount of isodecyl acrylate added is 100-130 mL, and the amount of azobisisobutyronitrile added is 15-40 g; the amount of acrylamide added to each liter of the additive liquid is 120-150 g; and the volume ratio between the additive liquid and the base liquid C in the polymerization liquid is 1-2:2-3.

[0021] Preferably, in step b2, the weight of the intermediate A immersed in each liter of the polymerization solution is 80-100 g.

[0022] Preferably, the step [3] specifically includes the following operations:

[0023] c1. Thulium nitrate, bismuth nitrate, 68% nitric acid and ammonium bromide by mass were added to deionized water and mixed to form a first reaction solution, the intermediate B was immersed in the reaction solution, reacted at room temperature for 10 to 14 hours, removed, and dried for 8 to 10 hours to obtain an intermediate C;

[0024] c2. Tellurium dioxide, bismuth nitrate, copper sulfide and 68% nitric acid by mass are added to deionized water and mixed to form a second reaction solution. The intermediate C is immersed in the reaction solution, reacted at room temperature for 6 to 8 hours, then taken out and dried for 6 to 10 hours to complete the assembly of BiCu2O6STe5 / Bi2BrTmO4 nanocrystals on the surface of polyacrylamide-isodecyl acrylate, and finally the composite photocatalytic material is obtained.

[0025] Preferably, in step c1, the mass concentration of nitric acid in the first reaction solution is 6-15%, the concentration of thulium nitrate is 110-130 g / L, the concentration of bismuth nitrate is 60-90 g / L, and the concentration of ammonium bromide is 90-130 g / L; the amount of intermediate B immersed in each liter of the first reaction solution is 120-140 g.

[0026] Preferably, in step c2, the amount of tellurium dioxide added to each liter of the second reaction solution is 40-80 g, the amount of bismuth nitrate added is 20-40 g, and the amount of copper sulfide added is 60-90 g; the mass concentration of nitric acid in the second reaction solution is 10-16%; the weight of the intermediate C immersed in each liter of the second reaction solution is 60-80 g.

[0027] Positive effects of the present invention: The composite catalytic material prepared by the method of the present invention is synthesized by polymerization reaction of acrylamide monomer and isodecyl acrylate monomer on the surface of foam copper, and then BiCu2O6STe5 / Bi2BrTmO4 nanocrystals are assembled on the surface of polyacrylamide-isodecyl acrylate. Among them, the polyacrylamide-isodecyl acrylate organic matter forms a main chain through conjugated connection, and has high electron mobility, so it has good conductive properties; in addition, the polyacrylamide-isodecyl acrylate organic matter has high light absorption rate and good visible light absorption characteristics; at the same time, due to the molecular thermal vibration mechanism, the polyacrylamide-isodecyl acrylate organic matter has outstanding photothermal conversion efficiency. BiCu2O6STe5 / Bi2BrTmO4 nanocrystals have the characteristics of wide absorption spectrum of visible light and ultraviolet light, and BiCu2O6STe5 / Bi2BrTmO4 nanocrystals have localized surface plasmon resonance effect, and the generation and relaxation of photogenerated electron-hole pairs have excellent photothermal conversion efficiency. The excellent photothermal conversion performance of the prepared foamed iron-based composite catalytic material can effectively activate the decomposition of peroxymonosulfate to produce sulfate free radicals with oxidative activity, and it also has the characteristics of multiple active sites for adsorbing rhodamine B.

[0028] In summary, the composite catalytic material prepared according to the present invention has a wide absorption spectrum and excellent and stable performance of photothermal activation of peroxymonosulfate to degrade Rhodamine B organic dye. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 It is a schematic diagram of the preparation process of the composite catalytic material of the present invention;

[0030] Figure 2 is a schematic diagram of the structure of the composite catalytic material of the present invention;

[0031] Figure 3 The residual RhB concentration of the simulated Rhodamine B organic dye wastewater treated under ultraviolet light and visible light in Example 1, Comparative Example 1 and Comparative Example 2 of the present invention;

[0032] Figure 4a , 4b 4 and 4c are relationship diagrams between the number of times of use and the residual RhB concentration when Example 1, Comparative Example 1 and Comparative Example 2 are repeatedly used to treat simulated Rhodamine B organic dye wastewater. DETAILED DESCRIPTION

[0033] Reference Figure 1 The present invention provides a method for preparing a composite catalytic material capable of degrading Rhodamine B in organic wastewater, comprising the following steps:

[0034] Step [1] loading isodecyl acrylate on the surface of the foamed iron substrate specifically comprises the following operations:

[0035] a1. Acrylic acid, 98% concentrated sulfuric acid and isodecyl alcohol are added to deionized water and mixed to form a base liquid A (the amount of acrylic acid added per liter of the base liquid A is 230 to 270 mL, the amount of isodecyl alcohol added is 140 to 210 mL, and the mass concentration of sulfuric acid in the base liquid A is 5-10%); phosphorus pentachloride is added to carbon tetrachloride and mixed to form a base liquid B (the amount of phosphorus pentachloride added per liter of the base liquid B is 20 to 40 g); the base liquid A and the base liquid B are mixed in a volume ratio of 3 to 5: 1 to 2 to obtain a load liquid;

[0036] a2. Immerse the foamed iron in an isodecyl acrylate loading liquid (the weight of the foamed iron substrate immersed in each liter of the loading liquid is 150-200 g), heat to 80-130°C, react for 2-4 hours, then cool to room temperature, and dry at room temperature for 10 to 14 hours to obtain a foamed iron with isodecyl acrylate loaded on the surface, recorded as intermediate A.

[0037] Step [2] synthesizing poly(acrylamide-isodecyl acrylate) on the surface of the foamed iron matrix by a polymerization reaction between acrylamide monomer and isodecyl acrylate monomer, specifically comprising the following operations:

[0038] b1. Add acrylic acid, isodecyl acrylate and azobisisobutyronitrile to ethanol and mix to form a base liquid C (the amount of acrylic acid added to the base liquid C is 60 to 100 mL, the amount of isodecyl acrylate added is 100 to 130 mL, and the amount of azobisisobutyronitrile added is 15 to 40 g); add acrylamide to deionized water to form an additive solution (the amount of acrylamide added to the additive solution is 120 to 150 g); mix the additive solution and the base liquid C in a volume ratio of 1 to 2:2 to 3 to obtain a polymerization solution.

[0039] b2. Immerse the intermediate A in the polymerization solution (the weight of the intermediate A immersed in each liter of the polymerization solution is 80-100 g), heat to 70-100°C, react for 10-14 hours, cool to room temperature, and dry at room temperature for 8 to 12 hours to obtain foamed iron with polyacrylamide-isodecyl acrylate loaded on the surface, recorded as intermediate B.

[0040] Step [3] assembling BiCu2O6STe5 / Bi2BrTmO4 nanocrystals on the surface of the poly(acrylamide-isodecyl acrylate) specifically comprises the following operations:

[0041] c1. Thulium nitrate, bismuth nitrate, nitric acid having a mass fraction of 68% and ammonium bromide are added to deionized water to form a first reaction solution having a nitric acid mass concentration of 6 to 15%, a thulium nitrate concentration of 110 to 130 g / L, a bismuth nitrate concentration of 60 to 90 g / L, and an ammonium bromide concentration of 90 to 130 g / L, and the intermediate B is immersed in the reaction solution (the amount of the intermediate B immersed in each liter of the first reaction solution is 120-140 g), reacted at room temperature for 10 to 14 hours, removed, and dried for 8 to 10 hours to obtain an intermediate C;

[0042] c2. Tellurium dioxide, bismuth nitrate, copper sulfide, and 68% nitric acid by mass are added to deionized water and mixed to form a second reaction solution (the amount of tellurium dioxide added per liter of the second reaction solution is 40-80 g, the amount of bismuth nitrate added is 20-40 g, the amount of copper sulfide added is 60-90 g, and the mass concentration of nitric acid is 10-16%), and the intermediate C is immersed in the reaction solution (the weight of the intermediate C immersed in each liter of the second reaction solution is 60-80 g), reacted at room temperature for 6-8 hours, taken out, and dried for 6-10 hours to complete the assembly of BiCu2O6STe5 / Bi2BrTmO4 nanocrystals on the surface of polyacrylamide-isodecyl acrylate, and finally the composite photocatalytic material (foamed iron-based BiCu2O6STe5 / Bi2BrTmO4 crystals @ polyacrylamide-isodecyl acrylate) is obtained, and its microstructure schematic diagram is shown as follows Figure 2 shown.

[0043] The preferred embodiments of the present invention are described below by way of example.

[0044] Example 1

[0045] Preferred embodiment 1 of the present invention provides a method for preparing a composite catalytic material capable of degrading rhodamine B in organic wastewater, comprising the following steps:

[0046] Step [1] loading isodecyl acrylate on the surface of the foamed iron substrate specifically comprises the following operations:

[0047] a1. Acrylic acid, 98% concentrated sulfuric acid and isodecyl alcohol were added to deionized water and mixed to form a base solution A (the amount of acrylic acid added per liter of the base solution A was 250 mL, the amount of isodecyl alcohol added was 170 mL, and the mass concentration of sulfuric acid in the base solution A was 8%); phosphorus pentachloride was added to carbon tetrachloride and mixed to form a base solution B (the amount of phosphorus pentachloride added per liter of the base solution B was 35 g); the base solution A and the base solution B were mixed in a volume ratio of 5:2 to obtain a load solution;

[0048] a2. Immerse the foamed iron in an isodecyl acrylate loading liquid (the weight of the foamed iron substrate immersed in each liter of the loading liquid is 160 g), heat to 100°C, react for 3 hours, then cool to room temperature, and dry at room temperature for 14 hours to obtain a foamed iron with isodecyl acrylate loaded on the surface, which is recorded as intermediate A.

[0049] Step [2] synthesizing poly(acrylamide-isodecyl acrylate) on the surface of the foamed iron matrix by a polymerization reaction between acrylamide monomer and isodecyl acrylate monomer, specifically comprising the following operations:

[0050] b1. Acrylic acid, isodecyl acrylate and azobisisobutyronitrile are added to ethanol and mixed to form a base liquid C (the amount of acrylic acid added to the base liquid C is 90 mL, the amount of isodecyl acrylate added is 120 mL, and the amount of azobisisobutyronitrile added is 30 g); acrylamide is added to deionized water to form an additive solution (the amount of acrylamide added to the additive solution is 140 g); the additive solution and the base liquid C are mixed in a volume ratio of 1:3 to obtain a polymerization solution.

[0051] b2. Immerse the intermediate A in the polymerization solution (the weight of the intermediate A immersed in each liter of the polymerization solution is 90 g), heat to 80°C, react for 12 hours, then cool to room temperature, and dry at room temperature for 10 hours to obtain foam iron with polyacrylamide-isodecyl acrylate loaded on the surface, which is recorded as intermediate B.

[0052] Step [3] assembling BiCu2O6STe5 / Bi2BrTmO4 nanocrystals on the surface of the poly(acrylamide-isodecyl acrylate) specifically comprises the following operations:

[0053] c1. Thulium nitrate, bismuth nitrate, 68% nitric acid and ammonium bromide were added to deionized water to form a first reaction solution having a nitric acid concentration of 10%, a thulium nitrate concentration of 120 g / L, a bismuth nitrate concentration of 80 g / L, and an ammonium bromide concentration of 110 g / L, and the intermediate B was immersed in the reaction solution (the amount of the intermediate B immersed in each liter of the first reaction solution was 130 g), and the reaction was removed at room temperature for 12 hours and dried for 9 hours to obtain an intermediate C;

[0054] c2. Add tellurium dioxide, bismuth nitrate, copper sulfide and 68% nitric acid by mass into deionized water, mix to form a second reaction solution (the amount of tellurium dioxide added per liter of the second reaction solution is 60 g, the amount of bismuth nitrate added is 30 g, the amount of copper sulfide added is 80 g, and the mass concentration of nitric acid is 12%), immerse the intermediate C in the reaction solution (the weight of the intermediate C immersed in each liter of the second reaction solution is 70 g), react at room temperature for 7 hours, then take out and dry for 8 hours to complete the assembly of BiCu2O6STe5 / Bi2BrTmO4 nanocrystals on the surface of polyacrylamide-isodecyl acrylate, and finally obtain the composite photocatalytic material, which is recorded as Example 1.

[0055] Comparative Example 1

[0056] This comparative example 1 provides a method for preparing a composite catalytic material capable of degrading rhodamine B in organic wastewater, comprising the following steps:

[0057] Step [1] loading isodecyl acrylate on the surface of the foamed iron substrate specifically comprises the following operations:

[0058] a1. Acrylic acid, 98% concentrated sulfuric acid and isodecyl alcohol were added to deionized water and mixed to form a base solution A (the amount of acrylic acid added per liter of the base solution A was 240 mL, the amount of isodecyl alcohol added was 190 mL, and the mass concentration of sulfuric acid in the base solution A was 6%); phosphorus pentachloride was added to carbon tetrachloride to form a base solution B (the amount of phosphorus pentachloride added per liter of the base solution B was 30 g); the base solution A and the base solution B were mixed in a volume ratio of 3:1 to obtain a load solution;

[0059] a2. Immerse the foamed iron in an isodecyl acrylate loading liquid (the weight of the foamed iron substrate immersed in each liter of the loading liquid is 160 g), heat to 90°C, react for 3 hours, then cool to room temperature, and dry at room temperature for 12 hours to obtain a foamed iron with isodecyl acrylate loaded on the surface, recorded as intermediate A.

[0060] Step [2] synthesizing poly(acrylamide-isodecyl acrylate) on the surface of the foamed iron matrix by a polymerization reaction between acrylamide monomer and isodecyl acrylate monomer, specifically comprising the following operations:

[0061] b1. Acrylic acid, isodecyl acrylate and azobisisobutyronitrile are added to ethanol and mixed to form a base liquid C (the amount of acrylic acid added to the base liquid C is 80 mL, the amount of isodecyl acrylate added is 110 mL, and the amount of azobisisobutyronitrile added is 20 g); acrylamide is added to deionized water to form an additive solution (the amount of acrylamide added to the additive solution is 130 g); the additive solution and the base liquid C are mixed in a volume ratio of 2:3 to obtain a polymerization solution.

[0062] b2. Immerse the intermediate A in the polymerization solution (the weight of the intermediate A immersed in each liter of the polymerization solution is 90 g), heat to 80°C, react for 12 hours, then cool to room temperature, and dry at room temperature for 10 hours to obtain foam iron with polyacrylamide-isodecyl acrylate loaded on the surface, which is recorded as intermediate B.

[0063] Step [3] assembling Bi2BrTmO4 nanocrystals on the surface of the poly(acrylamide-isodecyl acrylate) specifically comprises the following operations:

[0064] c1. Add thulium nitrate, bismuth nitrate, 68% nitric acid and ammonium bromide into deionized water, mix to form a first reaction solution with a nitric acid mass concentration of 8%, a thulium nitrate concentration of 120 g / L, a bismuth nitrate concentration of 70 g / L and an ammonium bromide concentration of 100 g / L, immerse the intermediate B in the reaction solution (the amount of the intermediate B immersed in each liter of the first reaction solution is 130 g), react at room temperature for 12 hours, take out, and dry for 9 hours to obtain the composite photocatalytic material, which is recorded as Comparative Example 1.

[0065] Comparative Example 2

[0066] This comparative example 2 provides a method for preparing a composite catalytic material capable of degrading rhodamine B in organic wastewater, comprising the following steps:

[0067] Step [1] loading isodecyl acrylate on the surface of the foamed iron substrate specifically comprises the following operations:

[0068] a1. Acrylic acid, 98% concentrated sulfuric acid and isodecyl alcohol were added to deionized water and mixed to form a base solution A (the amount of acrylic acid added per liter of the base solution A was 240 mL, the amount of isodecyl alcohol added was 180 mL, and the mass concentration of sulfuric acid in the base solution A was 6%); phosphorus pentachloride was added to carbon tetrachloride and mixed to form a base solution B (the amount of phosphorus pentachloride added per liter of the base solution B was 25 g); the base solution A and the base solution B were mixed in a volume ratio of 4:1 to obtain a load solution;

[0069] a2. Immerse the foamed iron in an isodecyl acrylate loading liquid (the weight of the foamed iron substrate immersed in each liter of the loading liquid is 170 g), heat to 100°C, react for 3 hours, then cool to room temperature, and dry at room temperature for 12 hours to obtain a foamed iron with isodecyl acrylate loaded on the surface, recorded as intermediate A.

[0070] Step [2] synthesizing poly(acrylamide-isodecyl acrylate) on the surface of the foamed iron matrix by a polymerization reaction between acrylamide monomer and isodecyl acrylate monomer, specifically comprising the following operations:

[0071] b1. Acrylic acid, isodecyl acrylate and azobisisobutyronitrile are added to ethanol and mixed to form a base liquid C (the amount of acrylic acid added to each liter of the base liquid C is 80 mL, the amount of isodecyl acrylate added is 120 mL, and the amount of azobisisobutyronitrile added is 30 g); acrylamide is added to deionized water to form an additive solution (the amount of acrylamide added to each liter of the additive solution is 140 g); the additive solution and the base liquid C are mixed in a volume ratio of 1:3 to obtain a polymerization solution.

[0072] b2. The intermediate A is immersed in the polymerization solution (the weight of the intermediate A immersed in each liter of the polymerization solution is 90 g), heated to 80°C, reacted for 12 hours, cooled to room temperature, and dried at room temperature for 10 hours to obtain a foamed iron with polyacrylamide-isodecyl acrylate loaded on the surface, which is recorded as Comparative Example 2.

[0073] In order to analyze the absorption spectrum characteristics of the photothermally activated persulfate degradation treatment of rhodamine B organic dye wastewater in Example 1, Comparative Example 1 and Comparative Example 2, the stability of photothermally activated persulfate and the performance of photothermally activated persulfate in degradation of rhodamine B organic dye, rhodamine B and potassium persulfate were dissolved in deionized water to form simulated rhodamine B organic dye wastewater with a rhodamine B concentration of 10 mg / L and a potassium persulfate concentration of 0.5 g / L. 100 ml of simulated rhodamine B organic dye wastewater was poured into a beaker, 6 g of Example 1, Comparative Example 1 and Comparative Example 2 were placed in the beaker, and ultraviolet light (λ=350 nm) and visible light (λ=530 nm) were used to irradiate Comparative Example 1, Comparative Example 2 and Example 1 for 40 minutes using a xenon lamp light source under the conditions of a working current of 20 A and a working voltage of 20 V. The residual concentration of rhodamine B was analyzed using an ultraviolet-visible spectrophotometer. The results are as follows: Figure 3 As shown in the figure, it can be seen that the residual RhB concentrations of persulfate degradation by ultraviolet light and visible light photothermal activation in Example 1 are only 0.04C0 and 0.06C0 respectively (C0 is the initial concentration of rhodamine B 10 mg / L), the residual RhB concentrations of ultraviolet light and visible light irradiation in Comparative Example 1 are 0.15C0 and 0.23C0 respectively, and the residual RhB concentrations of ultraviolet light and visible light irradiation in Comparative Example 2 reach 0.27C0 and 0.41C0 respectively. Under the above-mentioned treatment conditions and treatment time, Example 1, Comparative Example 1 and Comparative Example 2 are repeatedly used, and the relationship between the number of uses and the residual RhB concentration is as follows: Figure 4a -c, it can be seen from the figure that the residual RhB concentrations of the simulated Rhodamine B-containing organic dye wastewater in the fifth treatment under ultraviolet light and visible light in Example 1 are only 0.15C0 and 0.17C0, respectively; while the residual RhB concentrations of the simulated Rhodamine B-containing organic dye wastewater in the fifth treatment under ultraviolet light and visible light in Comparative Example 1 and Comparative Example 2 are 0.42C0, 0.53C0 and 0.66C0, 0.74C0, respectively.

[0074] In summary, the composite catalytic material prepared according to the present invention has a wide absorption spectrum and excellent and stable performance of photothermal activation of peroxymonosulfate to degrade Rhodamine B organic dye.

[0075] To illustrate in further detail, three additional examples are provided below.

[0076] Example 2

[0077] Preferred embodiment 2 of the present invention provides a method for preparing a composite catalytic material capable of degrading rhodamine B in organic wastewater, comprising the following steps:

[0078] Step [1] loading isodecyl acrylate on the surface of the foamed iron substrate specifically comprises the following operations:

[0079] a1. Acrylic acid, 98% concentrated sulfuric acid and isodecyl alcohol were added to deionized water and mixed to form a base solution A (the amount of acrylic acid added per liter of the base solution A was 230 mL, the amount of isodecyl alcohol added was 140 mL, and the mass concentration of sulfuric acid in the base solution A was 10%); phosphorus pentachloride was added to carbon tetrachloride and mixed to form a base solution B (the amount of phosphorus pentachloride added per liter of the base solution B was 20 g); the base solution A and the base solution B were mixed in a volume ratio of 3:2 to obtain a load solution;

[0080] a2. Immerse the foamed iron in an isodecyl acrylate loading liquid (the weight of the foamed iron substrate immersed in each liter of the loading liquid is 150 g), heat to 130°C, react for 2 hours, then cool to room temperature, and dry at room temperature for 10 hours to obtain a foamed iron with isodecyl acrylate loaded on the surface, recorded as intermediate A.

[0081] Step [2] synthesizing poly(acrylamide-isodecyl acrylate) on the surface of the foamed iron matrix by a polymerization reaction between acrylamide monomer and isodecyl acrylate monomer, specifically comprising the following operations:

[0082] b1. Acrylic acid, isodecyl acrylate and azobisisobutyronitrile are added to ethanol and mixed to form a base liquid C (the amount of acrylic acid added to the base liquid C is 60 mL, the amount of isodecyl acrylate added is 100 mL, and the amount of azobisisobutyronitrile added is 40 g); acrylamide is added to deionized water to form an additive solution (the amount of acrylamide added to the additive solution is 120 g); the additive solution and the base liquid C are mixed in a volume ratio of 2:3 to obtain a polymerization solution.

[0083] b2. Immerse the intermediate A in the polymerization solution (the weight of the intermediate A immersed in each liter of the polymerization solution is 100 g), heat to 70°C, react for 14 hours, cool to room temperature, and dry at room temperature for 12 hours to obtain foam iron with polyacrylamide-isodecyl acrylate loaded on the surface, which is recorded as intermediate B.

[0084] Step [3] assembling BiCu2O6STe5 / Bi2BrTmO4 nanocrystals on the surface of the poly(acrylamide-isodecyl acrylate) specifically comprises the following operations:

[0085] c1. Thulium nitrate, bismuth nitrate, nitric acid having a mass fraction of 68% and ammonium bromide were added to deionized water to form a first reaction solution having a nitric acid mass concentration of 6%, a thulium nitrate concentration of 110 g / L, a bismuth nitrate concentration of 90 g / L and an ammonium bromide concentration of 90 g / L, and the intermediate B was immersed in the reaction solution (the amount of the intermediate B immersed in each liter of the first reaction solution was 140 g), and the reaction was removed at room temperature for 10 hours and dried for 10 hours to obtain an intermediate C;

[0086] c2. Add tellurium dioxide, bismuth nitrate, copper sulfide and 68% nitric acid into deionized water and mix to form a second reaction solution (the amount of tellurium dioxide added per liter of the second reaction solution is 40 g, the amount of bismuth nitrate added is 20 g, the amount of copper sulfide added is 60 g, and the concentration of nitric acid is 10% by mass), immerse the intermediate C in the reaction solution (the weight of the intermediate C immersed in each liter of the second reaction solution is 80 g), react at room temperature for 6 hours, then take out and dry for 10 hours to complete the assembly of BiCu2O6STe5 / Bi2BrTmO4 nanocrystals on the surface of polyacrylamide-isodecyl acrylate, and finally obtain the composite photocatalytic material.

[0087] Example 3

[0088] Preferred embodiment 3 of the present invention provides a method for preparing a composite catalytic material capable of degrading rhodamine B in organic wastewater, comprising the following steps:

[0089] Step [1] loading isodecyl acrylate on the surface of the foamed iron substrate specifically comprises the following operations:

[0090] a1. Acrylic acid, 98% concentrated sulfuric acid and isodecyl alcohol were added to deionized water and mixed to form a base solution A (the amount of acrylic acid added per liter of the base solution A was 270 mL, the amount of isodecyl alcohol added was 210 mL, and the mass concentration of sulfuric acid in the base solution A was 5%); phosphorus pentachloride was added to carbon tetrachloride to form a base solution B (the amount of phosphorus pentachloride added per liter of the base solution B was 40 g); the base solution A and the base solution B were mixed in a volume ratio of 3: 1 to obtain a load solution;

[0091] a2. Immerse the foamed iron in an isodecyl acrylate loading liquid (the weight of the foamed iron substrate immersed in each liter of the loading liquid is 200 g), heat to 80°C, react for 4 hours, cool to room temperature, and dry at room temperature for 14 hours to obtain a foamed iron with isodecyl acrylate loaded on the surface, which is recorded as intermediate A.

[0092] Step [2] synthesizing poly(acrylamide-isodecyl acrylate) on the surface of the foamed iron matrix by a polymerization reaction between acrylamide monomer and isodecyl acrylate monomer, specifically comprising the following operations:

[0093] b1. Acrylic acid, isodecyl acrylate and azobisisobutyronitrile are added to ethanol and mixed to form a base liquid C (the amount of acrylic acid added to each liter of the base liquid C is 100 mL, the amount of isodecyl acrylate added is 130 mL, and the amount of azobisisobutyronitrile added is 15 g); acrylamide is added to deionized water to form an additive solution (the amount of acrylamide added to each liter of the additive solution is 150 g); the additive solution and the base liquid C are mixed in a volume ratio of 1:2 to obtain a polymerization solution.

[0094] b2. Immerse the intermediate A in the polymerization solution (the weight of the intermediate A immersed in each liter of the polymerization solution is 80 g), heat to 100°C, react for 10 hours, cool to room temperature, and dry at room temperature for 8 hours to obtain foam iron with polyacrylamide-isodecyl acrylate loaded on the surface, which is recorded as intermediate B.

[0095] Step [3] assembling BiCu2O6STe5 / Bi2BrTmO4 nanocrystals on the surface of the poly(acrylamide-isodecyl acrylate) specifically comprises the following operations:

[0096] c1. Thulium nitrate, bismuth nitrate, nitric acid having a mass fraction of 68% and ammonium bromide are added to deionized water to form a first reaction solution having a nitric acid mass concentration of 15%, a thulium nitrate concentration of 130 g / L, a bismuth nitrate concentration of 60 g / L, and an ammonium bromide concentration of 130 g / L, and the intermediate B is immersed in the reaction solution (the amount of the intermediate B immersed in each liter of the first reaction solution is 120 g), and the reaction is removed at room temperature for 14 hours and dried for 8 hours to obtain an intermediate C;

[0097] c2. Add tellurium dioxide, bismuth nitrate, copper sulfide and 68% nitric acid by mass into deionized water, mix to form a second reaction solution (the amount of tellurium dioxide added per liter of the second reaction solution is 80 g, the amount of bismuth nitrate added is 40 g, the amount of copper sulfide added is 90 g, and the concentration of nitric acid by mass is 16%), immerse the intermediate C in the reaction solution (the weight of the intermediate C immersed in each liter of the second reaction solution is 60-80 g), react at room temperature for 8 hours, then take out and dry for 6 hours to complete the assembly of BiCu2O6STe5 / Bi2BrTmO4 nanocrystals on the surface of polyacrylamide-isodecyl acrylate, and finally obtain the composite photocatalytic material.

[0098] Example 4

[0099] Preferred embodiment 4 of the present invention provides a method for preparing a composite catalytic material capable of degrading rhodamine B in organic wastewater, comprising the following steps:

[0100] Step [1] loading isodecyl acrylate on the surface of the foamed iron substrate specifically comprises the following operations:

[0101] a1. Acrylic acid, 98% concentrated sulfuric acid and isodecyl alcohol were added to deionized water and mixed to form a base solution A (the amount of acrylic acid added per liter of the base solution A was 256 mL, the amount of isodecyl alcohol added was 175 mL, and the mass concentration of sulfuric acid in the base solution A was 6.5%); phosphorus pentachloride was added to carbon tetrachloride to form a base solution B (the amount of phosphorus pentachloride added per liter of the base solution B was 30 g); the base solution A and the base solution B were mixed in a volume ratio of 5:2 to obtain a load solution;

[0102] a2. Immerse the foamed iron in an isodecyl acrylate loading liquid (the weight of the foamed iron substrate immersed in each liter of the loading liquid is 175 g), heat to 105°C, react for 3 hours, then cool to room temperature, and dry at room temperature for 12 hours to obtain a foamed iron with isodecyl acrylate loaded on the surface, recorded as intermediate A.

[0103] Step [2] synthesizing poly(acrylamide-isodecyl acrylate) on the surface of the foamed iron matrix by a polymerization reaction between acrylamide monomer and isodecyl acrylate monomer, specifically comprising the following operations:

[0104] b1. Acrylic acid, isodecyl acrylate and azobisisobutyronitrile are added to ethanol and mixed to form a base liquid C (the amount of acrylic acid added to the base liquid C is 80 mL, the amount of isodecyl acrylate added is 115 mL, and the amount of azobisisobutyronitrile added is 26 g); acrylamide is added to deionized water to form an additive solution (the amount of acrylamide added to the additive solution is 135 g); the additive solution and the base liquid C are mixed in a volume ratio of 2:3 to obtain a polymerization solution.

[0105] b2. Immerse the intermediate A in the polymerization solution (the weight of the intermediate A immersed in each liter of the polymerization solution is 90 g), heat to 85°C, react for 12 hours, then cool to room temperature, and dry at room temperature for 10 hours to obtain foam iron with polyacrylamide-isodecyl acrylate loaded on the surface, which is recorded as intermediate B.

[0106] Step [3] assembling BiCu2O6STe5 / Bi2BrTmO4 nanocrystals on the surface of the poly(acrylamide-isodecyl acrylate) specifically comprises the following operations:

[0107] c1. Thulium nitrate, bismuth nitrate, nitric acid having a mass fraction of 68% and ammonium bromide are added to deionized water to form a first reaction solution having a nitric acid mass concentration of 9%, a thulium nitrate concentration of 120 g / L, a bismuth nitrate concentration of 75 g / L, and an ammonium bromide concentration of 110 g / L, and the intermediate B is immersed in the reaction solution (the amount of the intermediate B immersed in each liter of the first reaction solution is 130 g), reacted at room temperature for 12 hours, removed, and dried for 9 hours to obtain an intermediate C;

[0108] c2. Add tellurium dioxide, bismuth nitrate, copper sulfide and 68% nitric acid by mass into deionized water, mix to form a second reaction solution (the amount of tellurium dioxide added per liter of the second reaction solution is 60 g, the amount of bismuth nitrate added is 30 g, the amount of copper sulfide added is 75 g, and the mass fraction of nitric acid concentration is 13%), immerse the intermediate C in the reaction solution (the weight of the intermediate C immersed in each liter of the second reaction solution is 70 g), react at room temperature for 7 hours, then take out and dry for 8 hours to complete the assembly of BiCu2O6STe5 / Bi2BrTmO4 nanocrystals on the surface of polyacrylamide-isodecyl acrylate, and finally obtain the composite photocatalytic material.

[0109] The above are only preferred embodiments of the present invention. It should be understood that the description of the above embodiments is only used to help understand the method and core ideas of the present invention, and is not used to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, etc. made within the ideas and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for preparing a composite catalytic material capable of degrading Rhodamine B in organic wastewater, characterized in that: The following steps are included: Step [1]: loading isodecyl acrylate on the surface of the foamed iron substrate; Step [2] synthesizing poly(acrylamide-isodecyl acrylate) on the surface of the foamed iron matrix by a polymerization reaction between acrylamide monomer and isodecyl acrylate monomer; Step [3] assembles BiCu2O6STe5 / Bi2BrTmO4 nanocrystals on the surface of the poly(acrylamide-isodecyl acrylate).

2. The method for preparing a composite catalytic material capable of degrading Rhodamine B in organic wastewater according to claim 1, characterized in that: The step [1] specifically includes the following operations: a1. Acrylic acid, 98% concentrated sulfuric acid and isodecyl alcohol were added to deionized water and mixed to form a base solution A; phosphorus pentachloride was added to carbon tetrachloride and mixed to form a base solution B; a certain amount of base solution A was mixed with base solution B to obtain a load solution; a2. Immerse the foamed iron in an isodecyl acrylate loading liquid, heat to 80-130°C, react for 2-4 hours, cool to room temperature, and dry at room temperature for 10 to 14 hours to obtain a foamed iron loaded with isodecyl acrylate on the surface, recorded as intermediate A.

3. The method for preparing a composite catalytic material capable of degrading Rhodamine B in organic wastewater according to claim 2, characterized in that: In step a1, the amount of acrylic acid added to each liter of the base liquid A is 230-270 mL, the amount of isodecyl alcohol added is 140-210 mL, and the mass concentration of sulfuric acid in the base liquid A is 5-10%; the amount of phosphorus pentachloride added to each liter of the base liquid B is 20-40 g; and the volume ratio between the base liquid A and the base liquid B in the load liquid is 3-5:1-2.

4. The method for preparing a composite catalytic material capable of degrading Rhodamine B in organic wastewater according to claim 2, characterized in that: In step a2, the weight of the foamed iron matrix immersed in each liter of the loading liquid is 150-200 g.

5. The method for preparing a composite catalytic material capable of degrading Rhodamine B in organic wastewater according to claim 1, characterized in that: The step [2] specifically includes the following operations: b1. Acrylic acid, isodecyl acrylate and azobisisobutyronitrile are added to ethanol and mixed to form a base liquid C; acrylamide is added to deionized water to form an additive liquid; a certain amount of the additive liquid is mixed with the base liquid C to obtain a polymer solution; b2. The intermediate A is immersed in the polymerization solution, heated to 70-100 ° C, reacted for 10-14 hours, cooled to room temperature, and dried at room temperature for 8 to 12 hours to obtain a foam iron loaded with polyacrylamide-isodecyl acrylate on the surface, recorded as intermediate B.

6. The method for preparing a composite catalytic material capable of degrading Rhodamine B in organic wastewater according to claim 5, characterized in that: In step b1, the amount of acrylic acid added to each liter of the base liquid C is 60-100 mL, the amount of isodecyl acrylate added is 100-130 mL, and the amount of azobisisobutyronitrile added is 15-40 g; the amount of acrylamide added to each liter of the additive liquid is 120-150 g; and the volume ratio between the additive liquid and the base liquid C in the polymerization liquid is 1-2:2-3.

7. The method for preparing a composite catalytic material capable of degrading Rhodamine B in organic wastewater according to claim 5, characterized in that: In step b2, the weight of the intermediate A immersed in each liter of the polymerization solution is 80-100 g.

8. The method for preparing a composite catalytic material capable of degrading Rhodamine B in organic wastewater according to claim 1, characterized in that: The step [3] specifically includes the following operations: c1. Thulium nitrate, bismuth nitrate, 68% nitric acid and ammonium bromide by mass were added to deionized water and mixed to form a first reaction solution, the intermediate B was immersed in the reaction solution, reacted at room temperature for 10 to 14 hours, removed, and dried for 8 to 10 hours to obtain an intermediate C; c2. Tellurium dioxide, bismuth nitrate, copper sulfide and 68% nitric acid by mass are added to deionized water and mixed to form a second reaction solution. The intermediate C is immersed in the reaction solution, reacted at room temperature for 6 to 8 hours, then taken out and dried for 6 to 10 hours to complete the assembly of BiCu2O6STe5 / Bi2BrTmO4 nanocrystals on the surface of polyacrylamide-isodecyl acrylate, and finally the composite photocatalytic material is obtained.

9. The method for preparing a composite catalytic material capable of degrading Rhodamine B in organic wastewater according to claim 8, characterized in that: In step c1, the mass concentration of nitric acid in the first reaction solution is 6-15%, the concentration of thulium nitrate is 110-130 g / L, the concentration of bismuth nitrate is 60-90 g / L, and the concentration of ammonium bromide is 90-130 g / L; the amount of intermediate B immersed in each liter of the first reaction solution is 120-140 g.

10. The method for preparing a composite catalytic material capable of degrading Rhodamine B in organic wastewater according to claim 8, characterized in that: In step c2, the amount of tellurium dioxide added to each liter of the second reaction solution is 40-80 g, the amount of bismuth nitrate added is 20-40 g, and the amount of copper sulfide added is 60-90 g. The mass concentration of nitric acid in the second reaction solution is 10-16%; the weight of the intermediate C immersed in each liter of the second reaction solution is 60-80 g.